Environmental conflicts, migration and governance - Krieger, Tim; Panke, Diana; Pregernig, Michael, 1968- (Bristol University Press, 2020)
A key driver of migration is environmental conflict, and this is only likely to increase with the effects of climate change. This urgent book responds to this and provides invaluable insights into urgent questions surrounding migration, climate change and conflict that will be of relevance to researchers across social science.